Ability of adenovirus 5 E1A proteins to suppress differentiation of BC3H1 myoblasts correlates with their binding to a 300 kDa cellular protein. - Mymryk, J S (1992)
We have used deletion mutants to define the regions in Ad5 E1A proteins necessary to suppress differentiation of mouse BC3H1 myoblasts. We examined the differentiation of cells infected at a low multiplicity with viruses containing the E1A deletions and constructed so as to produce only the smaller of the two major E1A proteins. Only four of the mutant viruses containing deletions within the N-terminal 69 residues failed to suppress differentiation as judged by changes in morphology and in levels of muscle-specific alpha-actin mRNA and creatine kinase activity. The results were confirmed by analyses of lines of cells stably transfected with representative E1A mutants. The mouse cellular proteins to which mutant E1A proteins bound were identified by immunoprecipitating E1A proteins specifically from infected BC3H1 cells and by analyzing the precipitates on denaturing gels. Bands of proteins of 300, 130, 107, 105 (the retinoblastoma product), and 60 kDa (cyclin A) were distinguished. Failure to suppress differentiation correlated with loss of binding to the 300-kDa protein but not to any of the others. The regions of E1A defined in this way have been shown to be required for several other activities, including enhancer repression and transformation. One function of the 300-kDa protein appears to be to facilitate the action of transcriptional enhancers of differentiation-specific genes.